2013
DOI: 10.3748/wjg.v19.i24.3831
|View full text |Cite
|
Sign up to set email alerts
|

Active treatments are a rational approach for hepatocellular carcinoma in elderly patients

Abstract: These results suggest that a therapeutic approach for HCC should not be restricted due to patient age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 12 publications
4
17
0
Order By: Relevance
“…Consequently, the number of operations performed on elderly patients is increasing. In the Japanese population, the overall incidence of hepatocellular carcinoma (HCC) has decreased due to the decreasing incidence of hepatitis C virus (HCV), while the rate of HCC in the absence of HCV, and of liver metastasis from colon cancer, has increased (13). The average age of patients undergoing hepatic resection has increased due to population aging (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the number of operations performed on elderly patients is increasing. In the Japanese population, the overall incidence of hepatocellular carcinoma (HCC) has decreased due to the decreasing incidence of hepatitis C virus (HCV), while the rate of HCC in the absence of HCV, and of liver metastasis from colon cancer, has increased (13). The average age of patients undergoing hepatic resection has increased due to population aging (1).…”
Section: Introductionmentioning
confidence: 99%
“…In the Japanese population, the overall incidence of hepatocellular carcinoma (HCC) has decreased due to the decreasing incidence of hepatitis C virus (HCV), while the rate of HCC in the absence of HCV, and of liver metastasis from colon cancer, has increased (13). The average age of patients undergoing hepatic resection has increased due to population aging (1). Several studies have reported on the usefulness and safety of hepatic resection for elderly patients: No differences in complications or prognosis were observed between this population and younger patients (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Suda et al [14] evaluated the survival of 740 patients who received various treatments for HCC between 1983 and 2011 and concluded that a therapeutic approach for HCC should not be restricted due to patient age.…”
Section: Treatment Flow Chart Of Hcc Overall and In Elderly Patientsmentioning
confidence: 99%
“…However, the treatments for HCC have progressed significantly over the last few years and Mirici-Cappa et al (5) demonstrated that the overall applicability of radical or effective HCC treatment may not be affected by age. Moreover, Suda et al (2) suggested that the therapeutic approach to HCC should not be restricted by patient age.…”
Section: Introductionmentioning
confidence: 99%
“…HCC principally develops on a background of chronic liver disease, particularly cirrhosis caused by hepatitis C or hepatitis B virus infection (1). In Japan, the median age of patients with HCC has been increasing gradually since 1986 (2). Elderly cancer patients often present with multiple comorbidities and age-related changes in the pharmacokinetics and pharmacodynamics of anticancer drugs that may affect chemotherapeutic regimens (3).…”
Section: Introductionmentioning
confidence: 99%